2022
DOI: 10.3390/diseases10040078
|View full text |Cite
|
Sign up to set email alerts
|

MALDI-TOF MS for Rapid Analysis of Bacterial Pathogens Causing Urinary Tract Infections in the Riyadh Region

Abstract: The successful treatment of bacterial disease is relied on selecting a suitable drug based on the type of bacteria and antimicrobial susceptibility testing. The study’s objective was to identify bacterial isolates from urine samples of patients from the community, followed by antimicrobial susceptibility testing of the isolated bacteria. A total of seventy urine samples were received in the clinical microbiology laboratory; out of which 18 culture-positive cultures and by direct identification using MALDI-TOF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…In a recent study, authors observed a considerable diversity amongst various isolates of E. coli. 34 E. coli isolates in this study were found scattered, which showed an evolutionary divergence. Two islolates, S-26 and S-31 with ST 1309 were found related with the standard ETEC (Enterotoxigenic E. coli) strains (Figure 1 & 2).…”
Section: Discussionmentioning
confidence: 46%
“…In a recent study, authors observed a considerable diversity amongst various isolates of E. coli. 34 E. coli isolates in this study were found scattered, which showed an evolutionary divergence. Two islolates, S-26 and S-31 with ST 1309 were found related with the standard ETEC (Enterotoxigenic E. coli) strains (Figure 1 & 2).…”
Section: Discussionmentioning
confidence: 46%
“…In the following years, open access protein mass spectrum libraries were created to facilitate microbial (virus, bacteria, fungi and yeast) characterization for clinical studies (Böhme et al, 2012). MALDI-TOF was first used in clinical microbiology (Seng et al, 2010;Erler et al, 2015;Patel, 2015;Anwer et al, 2022), followed by veterinary, soil, plant, food and water microbiology (Popović et al, 2017;Chun et al, 2022) and more recently for the aquatic pathogens (Jansson et al, 2020;Piamsomboon et al, 2020).…”
Section: History Applications and General Principles Of Maldi-tof Msmentioning
confidence: 99%
“…Using MALDI-TOF MS, rapid identification and clustering of K. pneumoniae isolates were performed from different restaurant sites in the Al-Qassim region of Saudi Arabia [61] . MALDI-TOF MS has also been used for the quick identification and typing of many other bacterial species [62] .…”
Section: Molecular Typing Of K Pneumoniaementioning
confidence: 99%